Expanding policy options for seed sector development - Spielman, David J.; Bishaw, Zewdie; López Noriega, Isabel; Otieno, Gloria; Vernooy, Ronnie; Muchugi, Alice; Degu, Tadesse Wuletaw; Yigezu, Yigezu A.; Ragasa, Catherine; Takeshima, Hiroyuki; Balié, Jean; Thiele, Graham; et al. (2021)
Lead authors: David J Spielman; Zewdie Bishaw; Isabel Lopez Noriega; Gloria Otieno; Ronnie Vernooy; Alice Muchugi; Tadesse Wuletaw Degu; Yigezu A. Yigezu; Catherine Ragasa; Hiroyuki Takeshima; Jean Balié; Graham Thiele; Jens-Peter Barnekow Lillesø; Bekele Kotu; Abdoul Aziz Niane; Tom van Mourik; Michael Halewood; Hakeem Ajeigbe; Norbert G. Maroya; Silver Tumwegamire; John Recha; Dawit Alemu